Does physical loading affect the speed and accuracy of tactical decision-making in elite junior soccer players? - Frybort, P.; Kokstejn, J.; Musalek, M.; Süss, V. (Journal of Sports Science & Medicine, 2016)
A soccer player`s capability to control and manage his behaviour in a game situation is a prerequisite, reflecting not only swift and accurate tactical decision-making, but also prompt implementation of a motor task during intermittent exercise conditions. The purpose of this study was to analyse the relationship between varying exercise intensity and the visual-motor response time and the accuracy of motor response in an offensive game situation in soccer. The participants (n = 42) were male, semi-professional, soccer players (M age 18.0 ± 0.9 years) and trained five times a week. Each player performed four different modes of exercise intensity on the treadmill (motor inactivity, aerobic, intermittent and anaerobic activity). After the end of each exercise, visual-motor response time and accuracy of motor response were assessed. Players` motion was captured by digital video camera. ANOVA indicated no significant difference (p = 0.090) in the accuracy of motor response between the four exercise intensity modes. Practical significance (Z-test = 0.31) was found in visual-motor response time between exercise with dominant involvement of aerobic metabolism, and intense intermittent exercise. A medium size effect (Z-test = 0.34) was also found in visual-motor response time between exercise with dominant involvement of aerobic metabolism and exercise with dominant involvement of anaerobic metabolism, which was confirmed by ANOVA (897.02 ± 57.46 vs. 940.95 ± 71.14; p = 0.002). The results showed that different modes of exercise intensity do not adversely affect the accuracy of motor responses; however, high-intensity exercise has a negative effect on visual-motor response time in comparison to moderate intensity exercise